RANCANG BANGUN SISTEM E-COMMERCE UNTUK PENJUALAN BARANG ANTIK PADA TOKO RENVIN ANTIQUE GALLERY - Kusuma, Aldo Surya; Dewanto, Adi (Journal of Information Technology and Education (JITED), 2024)
The development of digital technology has driven many businesses to utilize e-commerce systems in marketing their products. This research focuses on the design and implementation of a website-based e-commerce system to support the sale of antique items at Renvin Antique Gallery. The aim is to reach a wider market and enhance the online shopping experience for customers. A Research and Development (R&D) approach is adopted with stages including needs analysis, system design, implementation, testing, and evaluation. The research subjects involve the store owner and customers, with data collection techniques through interviews, observations, and questionnaire distribution. The research instrument utilizes the WebQual 4.0 model, which has been tested for validity and reliability, with data analysis using descriptive statistical methods aided by SPSS. The end result of this research is a web-based e-commerce system equipped with product catalog, shopping cart, checkout process, and PayPal payment integration features. Based on testing with WebQual 4.0, the system scores an average of 4.28 or 85.6%, which falls into the highly feasible category. The research concludes that the developed e-commerce system is able to meet user needs and provide a good online shopping experience. Suggestions for further development include regular optimization and updating of website content, more active promotion and marketing strategies, as well as periodic evaluations based on user feedback.